NATURE-BASED RELIGIONS, PLANT KINSHIP, AND SUSTAINABILITY - Biana, Hazel (Journal of Dharma, 2022)
The United Nations’ Sustainable Development Goals targets protecting the planet’s natural resources and re-establishing a sustainable planet for the next generations. The role that religion plays in the attainment of the SDGs lies in how it influences certain environmental actions and ethical choices. Modern nature-based religions, in particular, espouse the interconnectedness of humanity and nature, and reverence for Mother Earth. These revived nature belief systems are translated into practices and rituals where a type of familial or kin relationship between human beings and all its inhabitants is fostered. Human relationships with plants, for example, are venues where individuals may meld nature-based solutions and conservation practices. Plant kinship beliefs and plant caring are individual actions that may subsidise the agenda for peace and prosperity for people and the planet. In this paper, we uncover and revisit traditions that may address the sustainability agenda by critically engaging nature spirituality beliefs and plant kinship concepts.